Tripanossomíase por Trypanosoma vivax em pequenos ruminantes: descrição de surtos e infecção experimental da doença - Paiva, Erika de Souza (Universidade Federal Rural do Semi-Árido, 2009)
This research has considered Trypanosome s outbreaks by T. vivax that occurred in four groups of little ruminants in three towns of Alto Sertão da Paraíba in 2008 and recreated the disease experimentally in caprines and ovines, in order to relate the cardiac and central nervous system injuries with the parasite. For the statistics analyses the Test of Tukey (SAS) and the Qui-square (Epi Info 6.0) were done. The natural infection evaluation was done in the first outbreak (outbreak 1) and second (outbreak 2) semester of 2008, when the clinic signs were registered, parasitemia, rectal temperature, PCV and body score. 20% of adult caprine and ovine from each flock were chosen. It was noticed that in the first outbreak, the parasitemia was significantly bigger than in the second outbreak for both species, suggesting an acute and chronic stage of the disease. There was also a significant relation between the parasitemia, the temperature, the PCV and the body score in caprines and ovines. The anemia is a more evident clinical signal of the disease, followed by weight loss. At the PCR checkup, it was noticed that all the animals checked had the parasite in the blood. To evaluate the relation between the cardiac injuries with the T. vivax, 14 male ovines were used, SRD, disposed in 3 groups, being G1 the animals evaluated up to the 20th dpi (day pos infection), the G2, animals evaluated up to the 90th dpi and the G3 which is the control group, corresponding to the days of the groups treated. The isolated from T. vivax was from the outbreak occurred from Paraiba, being inoculated 1 ml containing 107 tripomastigotes. Clinical exams were done, hematological and anatomic-pathological. The animals presented hyperthermia, hydrothorax, ascites and hidropericardium. To the necropsy, the heart from an ovine from G2 presented evidences of cardiac failure. In the histological exam, hyaline necrosis was noticed, miocarditis with infiltrated inflammatory, besides fibrosis, suggestive of cardiac failure. In the evaluation of the injuries at the SNC related to T. vivax 12 male caprines were used, SRD, also disposed in three groups: G1 (animals evaluated in the acute stage of the disease), G2 (animals evaluated at the chronic stage of the disease) and G3 (control group). The isolated from T. vivax was due to an outbreak from ovines in Paraíba, being inoculated 1 ml containing 1.25 x 105 tripomastigotes. Within this study, besides the clinical exams, hematological and anatomic-pathological exams, the biochemical exam of the LCR were also done. The animals presented tetany, bruxism, opisthotonos and severe hyperthermia. In the exam of the LCR, there was a significant increase of the proteins in general and cellularity, as well as glicorrhachia and tubidez LCR. In the histological exam, meningoencephalitis was noticed, characterized by the presence of infiltrated inflammatory, besides morules cells (cells of Mott).
Trypanosome s by Trypanosome vivax in little ruminants: description of outbreaks and e experimental infection of the disease
Keywords: Little Ruminants; Tripanossomiases; Trypanosoma vivax; Pequenos Ruminantes; Tripanossomíase; Trypanosoma vivax; CIENCIAS AGRARIAS::MEDICINA VETERINARIA